ANALYSIS OF THE IMPACT OF SURAMADU BRIDGE DEVELOPMENT TO THE ECONOMIC GROWTH OF ITS CORE AND PERIPHERY REGIONS - Liza Setya Eka Hasul; Ari Dwi Jayanti (East Java Economic Journal, 2019)
East Java is one of the provinces in Indonesia which economic growth is above the national average. The city of Surabaya is the biggest contributor to the economy of East Java. Approximately 24% of the GDRP of East Java comes from this city. Although Bangkalan Regency is one of the bordering regencies of Surabaya, its economic growth is relatively low compared to the other bordering regencies. One of the government efforts to reducethe regional inequality is by building the Suramadu Bridge. According to the polar theory of growth, there are two possibilities that may occur as a result of regional interconnectivity. The first is centrifugal force which drives the population and its activities to move out of the core area followed by relocation of urban sectors and zones. The second is centripetal force which encourages population and activities to move towards the centeror core. The objective of this study is to assess the impact of the construction of the Suramadu National Bridge on economic growth in the core and periphery regions. Using Difference-in-Difference method, we found that the impact of the construction of the Suramadu Bridge on economic growth was greater in the periphery area than in the core area. This result might also imply that the development of Suramadu Bridge also resultedin the formation of centrifugal force which encouraged the economy to develop from the core to the periphery. JEL : R1, R4, O4, I1, I2